PENGARUH KOMISARIS INDEPENDEN, FINANCIAL DISTRESS, DAN AUDITOR SWITCHING TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI : (Studi Empiris Pada Perusahaan Sektor Healthcare Yang Terdaftar di Bursa Efek Indonesia Tahun) - Widjayanti, Indri; Rahmatika, Dien Noviany; Susetyo, Budi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Integrity of financial statements is an important characteristic that enables financial reporting to be transparent, honest, and fair, reflecting the condition of the company and can be trusted by stakeholders.Methods: . The technique used is descriptive, quantitatively, with secondary data from healthcare sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. The sample was taken using purposive sampling, resulting in 116 observations from 29 companies. The analysis was carried out using multiple linear regression and model-based regression analysis (MRA) with SPSS version 22.Results: The results indicate that, to some extent, independent commissionaires and financial distress have an adverse impact on the integrity of financial statements. In comparison, an auditor switching has no effect. Company size strengthens the influence of independent commissionaires and economic distress, but does not model the impact of auditor switching. Simultaneously, the three variables have a significant effect on the integrity of financial statements. These findings provide important insights for stakeholders in improving the transparency and accountability of financial statements in the healthcare sector. Keywords: Integrity of Financial Statements, Independent Commission, Financial Distress, Auditor Switching, Company Size